Gender and zoonotic pathogen exposure pathways in a resource-limited community, Mpumalanga, South Africa: A qualitative analysis. - Pallavi Oruganti; Elisabeth Root; Violet Ndlovu; Philemon Mbhungele; Ilana Van Wyk; Amanda M Berrian (Public Library of Science (PLoS), 2023)
The Mnisi community is a livestock-dependent community neighboring the Great Limpopo Transfrontier Conservation Area in South Africa. Here, zoonotic pathogens contribute to as many as 77% of cases of acute febrile illness. Previous gender-disaggregated analysis in the community has shown that men and women have different risks of zoonotic illness, suggesting that exposure routes for zoonotic infections should be further explored to inform gender-sensitive risk mitigation strategies. Using a One Health approach and ethnographic methodology, we examined interactions between community residents, domestic animals, and the built and natural environment to investigate potential exposure pathways for zoonotic infections from a gendered perspective. We combined data from direct household observations and focus group discussions on previously identified gendered tasks such as domestic animal care, water collection, and food preparation, and how and by whom these tasks were performed. We noted gender differences for household tasks, animal care duties, and environmental exposure. Both men and women access grazing land but for different tasks (water collection-females, cattle grazing-males), and both men and women experience more time in the bush in recent years due to decreased water availability. From observations, it was noted that men wore covered protective work clothes (such as long trousers and closed-toe shoes) more commonly than women did; women did not often wear these for household duties including water collection in the bush. We recommend that these gender-typed roles serve as critical control points for zoonotic pathogen exposure. For example, tick-bite exposure prevention should be directed at both men and women based on their daily activities, but prevention in men should target exposure from cattle and prevention in women should focus on personal protective measures during water and firewood collection. These findings can contribute to a more detailed understanding of the role of human behavior and critical control points for zoonotic disease-a significant contributor to acute febrile illness in this rural, resource-limited setting.